The Application of Good Agriculture Practices(GAP) of Shallot in Bantul Regency - Suharni Suharni; Lestari Rahayu Waluyati; Jamhari Jamhari (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2017)
Bantul Regency is one of the center of shallots in Indonesia, but its productivity is low. In 2015, the productivity of shallots in Bantul Regency was 7.66 tons/ha. The application of Good Agriculture Practices (GAP) is a form of technology adoption aiming to improve the shallot productivity.The purposes of this study are to determine the level of application of shallots GAP in Bantul Regency and to find out the factors influencing the application such as land area, farmers’ age, farmers’ education, farming experience, availability of farm inputs, and extension service frequency. Purposive technique was used to determine the research location. Sanden and Kretek districts were discovered since these areas are the production centers of shallots in Bantul Regency. The study involved the respondents consisting of sixty shallot farmers, thirty people from Kretek District and the other thirty people from Sanden District who were determined by simple random sampling. This research used scoring technique with Likert scale to measure the application level of GAP. Multiple linear regression analysis was used to understand the factors affecting the application of GAP of shallots. Result showed that the application of GAP of shallots in Bantul Regency is low. The factors of land area, farmers’ education, farming experience, and availability of farm inputs means infl uence the application level of GAP of shallots significantly.